MANAJEMEN SDM DI LEMBAGA PENDIDIKAN UNTUK PENINGKATAN KUALITAS PENDIDIKAN - Ulfah, Maria (Mimbar Administrasi Mandiri, 2024)
Human Resource Management (HRM) in educational institutions covers crucial aspects related to teachers, educational staff and structural administration. Also known as educator and educational management, this field plays a vital role in achieving national educational goals. This management process involves human resource planning, including recruitment, selection, placement, remuneration, reward, training, development and dismissal. The quality of HR in educational institutions has a major impact on the outcomes and quality of graduates. HR planning has two main dimensions: quantitative and qualitative. Quantitative planning focuses on estimating the number of staff required, while qualitative planning is concerned with the qualifications and requirements appropriate to the position or job in the future. In the context of education, effective human resource management is essential to ensure optimal performance and adaptation of educators to advances in technology and science. This article examines the definition, objectives, roles and functions of HRM in education and related activities such as planning, selection, orientation, performance management, reward, career development and dismissal. Emphasis is placed on the importance of HRM in building a qualified teaching workforce, which in turn will improve the quality of education and produce reliable, creative and accomplished human resources. Keywords: Human Resource Management, Training and education, Human Resource Planning, Quality of educators